PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE iPhone - Nadilla Febrianty; Safaruddin Safaruddin (Universitas Dharmawangsa, 2023)
Brand image and price also become a determining factor for someone in making a purchasing decision. Brand image is a number of images, impressions, and beliefs that a person has towards an object. If a product already has an appropriate price, and a brand image has been formed in the eyes of the public, then the company does not need to hesitate in providing a price above the average because it is likely that consumers will still buy it. This study aims to determine the effect of brand image and price on purchasing decisions for iPhone smartphone products. This type of research is quantitative research. The sampling method used was purposive sampling. The analytical method used is Multiple Linear Regression by testing the hypothesis using SPSS 25. The results of multiple linear regression calculations, Y = 1.507 + 0.458X1 + 0.492X2 + e, explain that the independent variables brand image and price have a positive effect on the dependent variable on purchasing decisions. The results of the test of the coefficient of determination show that brand image and price variables influence purchasing decisions by 53,6% and the rest are influenced by other variables not examined in this study.